ASSESSMENT OF TAXABILITY OF LOCAL BUDGETS IN THE REGIONS OF UKRAINE IN CONDITIONS OF DECENTRALIZATION - Bacho , R.; Pataki , G.; Illar , E. (The actual problems of regional economy development, 2020)
The article scientifically substantiates the need to study the mechanism of ensuring the taxability of local governments in the regions of Ukraine on the example of Uzhhorod city, because in the context of the political and economic crisis in Ukraine, the problems of increasing the role of local taxes and fees as a tool for filling local budgets’ revenue remain incompletely resolved. The purpose of the scientific article is to study the role of local taxes and fees as a way to strengthen decentralization processes in the regions of Ukraine and to analyze the tax provision of Uzhhorod city in Transcarpathian region. To solve the tasks in this study such research methods are used as: comparison, analysis, synthesis, economic and statistical methods, as well as the method of graphical representation of research results. The scientific novelty of the obtained results is the improvement of the local taxation system mechanism due to the introduction of changes in the composition of local tax payments and its individual elements. The practical significance of the research is in the scientific substantiation of the existing difficulties of financial decentralization in the regions, which is manifested in the high dependence of the Transcarpathian region on subsidies and subventions, to eliminate which local governments need to increase tax revenues (primarily local revenues and fees) and increase budget autonomy. It is concluded that since 2016 the taxability of the region begins to grow, but due to the high dependence of the region on subsidies and subventions, local governments need to increase the amount of tax revenues, primarily through revenues from local taxes and fees, and increase the autonomy of the local budget.